Azi E.A. The significance of Zhyrau-poetic art in the culture of the Turkic peoples (Journal of Philosophy, Culture and Political Science, 2025)
In the article, the images of people who influenced the life of the Turkic peoples and contributed to the development of nomadic culture are studied from various angles and find a scientific character. The worldview of the zhiraus, who lead many people to education and knowledge with their special qualities, is analyzed from a cultural and philosophical point of view, and their influence on the formation of public consciousness is considered as much as possible. The study focuses on the tradition of singing not only as an art, but also as a cultural phenomenon that reflects the spiritual and philosophical aspects of society. The stages of historical development of the zhirauk tradition and their place in field culture are shown, and their influence on later poets is discussed. Determining the peculiarities of martial arts originating from ancient times, paying attention to the fact that they are an old school that has reached later consequences, opens the way to weighting the tradition of martial arts as a branch of martial arts. It must be admitted that the amazing images of the zhiraus, which played a special role in the Kazakh society in the past, are still not taking their proper place in the history of culture. The image of the herdsmen reached through the memories they left behind and clarified their place in society. We must openly say that their fighting spirit, which inspires the masses as well as military campaigns, is a high symbol of true patriotism. This work suggests that the folk tradition of past historical periods and today is a cultural form that has a positive influence on society.Key words: Culture, society, folklore, joy, tradition, philosophy, Turks, nomads, music, mood.